Ekonomi Dalam Pandangan Islam dan Perannya Dalam Peningkatan Daya Saing Sumber Daya Manusia - Suminto, Ahmad; Ramdani Harahap, Soritua Ahmad; Zulqurnaini, Ahmad Budi (Invest Journal of Sharia & Economic Law, 2021)
This study aims to explain the economy from an Islamic perspective: and its role in increasing human resources and the economic development of Islam. This study uses a library research method with a descriptive-analytic qualitative approach, namely explaining and describing the object of research and then analyzing it from the perspective of the Islamic economic system. The results of this study indicate that, First, Islam views the economy as implemented with an attitude towards property ownership, absolute ownership of everything on earth belongs to Allah SWT. Human ownership is only relative, limited to carrying out the mandate of managing and utilizing according to His provisions. The status of assets in Islam is a mandate or deposit (as a truth) from Allah SWT to humans who have the capacity to be His creatures. Meanwhile, from the point of view of monotheism, humans as economic subjects are only limited to trustees. Second, the concept of Islamic economic development demands and makes humans to awaken human nature, namely the birth of a balance between happiness in the world and in the hereafter. This role has implications for the concern for development in Islam itself which emphasizes both physical and metaphysical elements. In addition to physical indicators, Islamic development also pays close attention to moral and spiritual aspects that are not shared by conventional development focus. The concepts of tawhid, khilafah, and 'are inseparable from the foundations of economic development in Islam.